Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

The Diagnostic and Prognostic Value of Neuropsychological Assessment in Memory Clinic Patients. - Jansen, Willemijn J; Handels, Ron L H; Visser, Pieter Jelle; Aalten, Pauline; Bouwman, Femke; Claassen, Jurgen; van Domburg, Peter; Hoff, Erik; Hoogmoed, Jan; Leentjens, Albert F G; Rikkert, Marcel Olde; Oleksik, Ania M; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Neuropsychological testing has long been embedded in daily clinical practice at memory clinics but the added value of a complete neuropsychological assessment (NPA) to standard clinical evaluation is unknown. OBJECTIVE: To evaluate the added diagnostic and prognostic value of NPA to clinical evaluation only in memory clinic patients. METHODS: In 221 memory clinic patients of a prospective cohort study, clinical experts diagnosed clinical syndrome (subjective cognitive impairment (SCI), mild cognitive impairment (MCI), or dementia) and etiology (Alzheimer's disease (AD) or no AD), and provided a prognosis of disease course (decline or no decline) before and after results of NPA were made available. The reference standard was a panel consensus based on all clinical information at baseline and up to 2 follow-up assessments. RESULTS: With NPA data available, clinicians changed their initial syndromal diagnosis in 22% of patients, and the etiological diagnosis as well as the prognosis in 15%. This led to an increase in correctly classified cases of 18% for syndromal diagnosis, 5% for etiological diagnosis, and 1% for prognosis. NPA data resulted in the largest improvement in patients initially classified as SCI (syndrome: 93.3% (n = 14) correctly reclassified, etiology: net reclassification improvement [NRI] = 0.61, prognosis: NRI = 0.13) or MCI (syndrome: 89.3% (n = 23) correctly reclassified, etiology: NRI = 0.17, prognosis: NRI = 0.14), while there was no improvement in patients with dementia (syndrome: 100% (n = 1) correctly reclassified, etiology: NRI = -0.05, prognosis: NRI = -0.06). Overall, inclusion of NPA in the diagnostic process increased confidence in all diagnoses with 6-7%. CONCLUSION: Administration of a complete NPA after standard clinical evaluation has added value for diagnosing cognitive syndrome and its underlying etiology in patients regarded as non-demented based on the first clinical impression.

White Matter Hyperintensities Potentiate Hippocampal Volume Reduction in Non-Demented Older Individuals with Abnormal Amyloid-β. - Freeze, Whitney M; Jacobs, Heidi I L; Gronenschild, Ed H; Jansen, Jacobus F A; Burgmans, Saartje; Aalten, Pauline; Clerx, Lies; Vos, Stephanie J; van Buchem, Mark A; Barkhof, Frederik; van der Flier, Wiesje M; Verbeek, Marcel M; et al. (J Alzheimers Dis, 2017)
Cerebral small vessel disease (cSVD) and amyloid-β (Aβ) deposition often co-exist in (prodromal) dementia, and both types of pathology have been associated with neurodegeneration. We examined whether cSVD and Aβ have independent or interactive effects on hippocampal volume (HV) in a memory clinic population. We included 87 individuals with clinical diagnoses of Alzheimer's disease (AD) (n = 24), mild cognitive impairment (MCI) (n = 26), and subjective cognitive complaints (SCC) (n = 37). cSVD magnetic resonance imaging markers included white matter hyperintensity (WMH) volume, lacunar infarct presence, and microbleed presence. Aβ pathology was assessed as cerebrospinal fluid-derived Aβ1 - 42 levels and dichotomized into normal or abnormal, and HV was determined by manual volumetric measurements. A linear hierarchical regression approach was applied for the detection of additive or interaction effects between cSVD and Aβ on HV in the total participant group (n = 87) and in the non-demented group (including SCC and MCI individuals only, n = 63). The results revealed that abnormal Aβ and lacunar infarct presence were independently associated with lower HV in the non-demented individuals. Interestingly, Aβ and WMH pathology interacted in the non-demented individuals, such that WMH had a negative effect on HV in individuals with abnormal CSF Aβ42 levels, but not in individuals with normal CSF Aβ42 levels. These associations were not present when individuals with AD were included in the analyses. Our observations suggest that relatively early on in the disease process older individuals with abnormal Aβ levels are at an increased risk of accelerated disease progression when concomitant cSVD is present.

Added Prognostic Value of Cerebrospinal Fluid Biomarkers in Predicting Decline in Memory Clinic Patients in a Prospective Cohort. - Handels, Ron L H; Joore, Manuela A; Vos, Stephanie J B; Aalten, Pauline; Ramakers, Inez H G B; Rikkert, Marcel Olde; Scheltens, Philip; Jansen, Willemijn J; Visser, Pieter-Jelle; van Berckel, Bart M N; van Domburg, Peter; Smid, Machiel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Limited information is available on short-term prognosis of Alzheimer's disease (AD) biomarkers in cerebrospinal fluid (CSF) in addition to routine diagnostic workup. OBJECTIVE: This study aims to investigate the added prognostic value of AD CSF biomarkers. METHODS: In a prospective cohort study, clinical experts predicted cognitive and functional symptoms in 114 memory clinic patients by assessing comprehensive routine diagnostic test information (patient history, and physical, neurological, psychiatric, neuropsychological, and MRI examinations), without and with CSF biomarkers. The reference standard was the 'observed clinically relevant decline' using baseline and 1- and 2-year follow-up information. RESULTS: Decline over a 2-year period was observed in 51% of all participants (3% in SMC, 48% in MCI, 90% in mild dementia). In the total sample, the accuracy of predicted decline did not differ significantly between routine assessment without (79% correctly predicted) and with (74% correctly predicted) CSF biomarkers. Subgroup analyses revealed 25 (83%) correct predictions in SMC, 30 (68%) in MCI, and 35 (88%) in dementia without the use of CSF; and 21 (70%), 27 (61%), and 36 (90%), respectively, with the use of CSF in addition to the routine assessment. CONCLUSION: AD CSF biomarkers did not increase accuracy of 2-year prognosis of cognitive and functional decline when added to routine diagnostic workup. This suggests that the standard diagnostic workup without CSF biomarkers allows fairly accurate predictions for the short-term course of symptoms. Routine AD biomarkers in CSF have limited prognostic value over 2 years in persons with a suspected cognitive disorder.